Peningkatan Hasil Belajar Matematika dengan Media Google Classroom dan WhatsApp Sebagai Media Pembelajaran Daring pada Masa Pandemi Covid-19 bagi Siswa Kelas XII Busana 2 SMK Negeri 3 Baubau - Amlin Amlin (Universitas Pendidikan Mandalika, 2021)
This study aims to describe the improvement of student learning outcomes in mathematics subjects in statistics through Google Classroom and WhatsApp media. This research is a classroom action research in which the teacher plays a direct role in the online learning process. The subjects in this study were 32 students of class XII Busana 2 SMK Negeri 3 Baubau and the object of this research was to increase student learning outcomes with Google Classroom and WhatsApp media. The research instrument uses a test (daily test) in the form of an essay. The test is used to find out the results of learning mathematics. Based on the data analysis of students' mathematics learning outcomes in cycle I, there were 23 students who completed (71.88 %) and those who had not completed 9 (28.12 %), while in cycle II who completed it became 27 students (84.38 %) and unfinished 5 students (15.62 %) with an increase in the average value of the cycle I is 73.13 while the average value of the cycle II is 81.56 which has increased significantly, so based on the results of the data analysis obtained it can be concluded that with Google Classroom and WhatsApp media can improve student learning outcomes for class XII Busana 2 SMK Negeri 3 Baubau